PENERAPAN BALANCED SCORECARD PADA PERUSAHAAN JASA DI INDONESIA - Markus Djohan Utama; Ririn Breliastiti (Jurnal Akuntansi Bisnis, 2017)
Each company must have objectives that must be achieved. The main objective of the company is trying to make a profit as much as possible, where the profit is often used for business development. At this time, the popular method of performance measurement is the Balanced Scorecard. This method has been integrated with various methods of business strategy is expected to improve the company's performance significantly. Balanced Scorecard is a measurement method for measuring the company's performance in the future by considering four perspectives to measure the performance of the company are financial perspective, customer perspective, internal business process, and learning-growth perspective. This study aims to determine the application of Balanced Scorecard according to four perspectives and results of their performance according to the Balanced Scorecard measures for the three service companies under investigation. This research is a descriptive study based on observations carried out at three services company in Indonesia. Research on the application of balanced scorecard will be performed at three selected service companies, namely PT Fast Food Indonesia, PT Graha Layar Prima and PT Kristamedia Primary. Research results that the three companies have a Balanced Scorecard approach is a bit different, but still using the same four perspectives. Determination of the weight and the score is determined by the company taking into account the targets to be achieved for each perspective. The indicators used for each perspective also vary, depending on the target to be achieved, and the types of indicators can also vary. The three companies produce good Balanced Scorecard, which illustrates that the financial and non-financial performance can work in harmony and balance to achieve the goals set.Keywords: Balanced Scorecard